2019
DOI: 10.1038/s41598-019-43055-3
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of multifunctional titanium surfaces by producing hierarchical surface patterns using laser based ablation methods

Abstract: Textured implant surfaces with micrometer and sub-micrometer features can improve contact properties like cell adhesion and bacteria repellency. A critical point of these surfaces is their mechanical stability during implantation. Therefore, strategies capable to provide both biocompatibility for an improved implant healing and resistance to wear for protecting the functional surface are required. In this work, laser-based fabrication methods have been used to produce hierarchical patterns on titanium surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…Wu et al, 2011b). A study showed that holes or craters larger than the bacteria in the surface seem to inhibit the formation of bacteria colonies (Epperlein et al, 2017;C. Zwahr et al, 2019a).…”
Section: Accepted Articlementioning
confidence: 99%
“…Wu et al, 2011b). A study showed that holes or craters larger than the bacteria in the surface seem to inhibit the formation of bacteria colonies (Epperlein et al, 2017;C. Zwahr et al, 2019a).…”
Section: Accepted Articlementioning
confidence: 99%
“…First, single-scale textures were produced using both technologies to understand the morphology evolution as a function of the processing parameters and its influence on the wettability characteristics. The targeted DLW texture should not only provide an underlying roughness before the DLIP process to promote a high hydrophobicity, as already demonstrated in earlier publications [ 38 , 48 ], but also it should serve to protect the smaller features produced by DLIP [ 49 ].…”
Section: Fabrication Of Single- and Multi-scaled Texturesmentioning
confidence: 89%
“…By roughening the implant surface, the healing of the bone can be improved significantly. On the other hand, a very important requirement regarding the implant surfaces are their antibacterial properties [60]; therefore the surface structures with the features slightly smaller than the bacteria size, or the hole/crater-like structures slightly larger than the bacteria size, are used. As documented in this study, the moderately rough surfaces can be produced by laser machining when using lower energy densities (surface S1).…”
Section: Discussionmentioning
confidence: 99%